Effects of CGRP-Primed Dental Pulp Stem Cells on Trigeminal Sensory Neurons. (October 2021) - Michot, B.; Casey, S.M.; Gibbs, J.L.
Dental pulp stem cells (DPSCs) are important in tooth physiology, contributing to development, repair, regeneration, and immunomodulatory processes. However, their role in inflammatory mechanisms underlying pulpitis is not well understood. We evaluated the influence of DPSCs stimulated with calcitonin gene-related peptide (CGRP), a proinflammatory neuropeptide, on the expression of mediators released from DPSCs and the effect of these mediators on sensory neuron activity. Human DPSCs were treated with either control media or media containing CGRP (10 −8  M) for 7 d, and the conditioned media (CM) containing DPSC-released mediators was collected. The expression of cytokines and chemokines from DPSCs was evaluated by reverse transcription quantitative polymerase chain reaction. The effects of the CM from CGRP-primed DPSCs (primed DPSC-CM) were evaluated on sensory afferents by using primary cultures of mouse trigeminal neurons and an organotypic model of cultured human pulp slices. Mouse trigeminal neurons and human pulp explants were pretreated for 24 h with control or primed DPSC-CM and then stimulated with capsaicin. Afferent activity was measured by quantifying the response to capsaicin via live cell calcium imaging in mouse neurons and CGRP released from pulp explants. Gene expression analysis showed that primed DPSCs overexpressed some proinflammatory cytokines and chemokines, including chemokines CXCL1 and CXCL8, which are both agonists of the receptor CXCR2 expressed in sensory neurons. Primed DPSC-CM increased human pulp sensory afferent activity as compared with control DPSC-CM. Similarly, primed DPSC-CM increased the intensity of calcium responses in cultured mouse trigeminal neurons. Furthermore, the CXCR2 antagonist SB225002 prevented trigeminal neuron sensitization to capsaicin induced by primed DPSC-CM. In conclusion, mediators released by DPSCs, primed with the proinflammatory mediator CGRP, induce neuronal sensitization through CXCR2 receptor. These data suggest that DPSCs might contribute to pain symptoms that develop in pulpitis.